Controlling threshold in soil salinity when planting spring wheat and sequential cropping silage corn in Northern Xinjiang using drip irrigation - Wang, Zhenhua; Zhou, Bo; Pei, Lei; Zhang, Jinzhu; He, Xinlin; Lin, Henry (International Journal of Agricultural and Biological Engineering, 2018)
Xinjiang Region of China is one of the most typical and representative arid areas worldwide, along with severe soil salinization issue. Planting spring wheat and sequential cropping silage corn in Northern Xinjiang using drip irrigation has become an effective way to relieve soil salinity stress, which improves the simple agricultural structure in the past and ensures food security in this area. However, neither the effects of different soil salinities on the growth and yield of spring wheat and silage corn, nor their desalination effect correspondingly was clear until now. Therefore, a pot experiment was conducted at Shihezi, Xinjiang from March to June 2015. The study aimed to establish the quantitative correlations between the parameters mentioned above and came up with the appropriate soil salinity threshold in Northern Xinjiang area. The results confirmed that the soils in all treatments were desalinated after the whole growth period, and the decreasing rates varied within 18.89%-44.08% and 11.06%-30.83% for two plants, which showed linear and quadratic correlations with initial soil salinity, respectively (R2 > 0.92**, p < 0.05). Meanwhile, higher soil salinity would inhibit crop growth and yield, and the initial soil salinity also represented the negative quadratic correlations with growth parameters (R2 > 0.92**, p <0.01). The inhibition effect was enhanced with larger initial soil salinity. After the comprehensive consideration of soil salinity variation, crop growth and yield, the initial soil salinity was recommended under 8.91 g/kg and 5.54 g/kg to plant spring wheat and sequential cropping silage corn in Northern Xinjiang using drip irrigation. Keywords: soil salinity, drip irrigation, spring wheat sequential silage corn, quantitative correlations, critical controlling threshold DOI: 10.25165/j.ijabe.20181102.3621 Citation: Wang Z H, Zhou B, Pei L, Zhang J Z, He X L, Lin H. Controlling threshold in soil salinity when planting spring wheat and sequential cropping silage corn in Northern Xinjiang using drip irrigation. Int J Agric & Biol Eng, 2018; 11(2): 108–114.